2013
DOI: 10.1371/journal.pone.0070397
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin: A Distinct Fate of Neurogenin3 Positive Progenitor Cells in the Embryonic Pancreas

Abstract: Neurogenin3+ (Ngn3+) progenitor cells in the developing pancreas give rise to five endocrine cell types secreting insulin, glucagon, somatostatin, pancreatic polypeptide and ghrelin. Gastrin is a hormone produced primarily by G-cells in the stomach, where it functions to stimulate acid secretion by gastric parietal cells. Gastrin is expressed in the embryonic pancreas and is common in islet cell tumors, but the lineage and regulators of pancreatic gastrin+ cells are not known. We report that gastrin is abundan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
41
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 43 publications
7
41
0
Order By: Relevance
“…the pig (Capella et al 1978, Alumets et al 1983) and gastrinproducing G-cells have been demonstrated in the rat pancreas during neonatal development, while such cells are present, albeit in small numbers, in the pancreas of adult cat and dog (Larsson et al 1976a). Recently, G-cells have also been found to be a distinct islet cell type in mice during development (Suissa et al 2013).…”
Section: Enterochromaffin-cells and G-cellsmentioning
confidence: 99%
“…the pig (Capella et al 1978, Alumets et al 1983) and gastrinproducing G-cells have been demonstrated in the rat pancreas during neonatal development, while such cells are present, albeit in small numbers, in the pancreas of adult cat and dog (Larsson et al 1976a). Recently, G-cells have also been found to be a distinct islet cell type in mice during development (Suissa et al 2013).…”
Section: Enterochromaffin-cells and G-cellsmentioning
confidence: 99%
“…NEUROG3 expression peaks during the major endocrine cell differentiation phase of the embryonic pancreas, known as 'secondary transition'. During this period gastrin and its high-affinity receptor cholecystokinin B receptor (CCKBR) are expressed within the endocrine domain of the developing pancreas (Larsson et al 1976, Suissa et al 2013. In post-natal life, pancreatic gastrin and CCKBR expression declines along with b-cell neogenesis (Rooman et al 2001, Suissa et al 2013.…”
mentioning
confidence: 99%
“…During this period gastrin and its high-affinity receptor cholecystokinin B receptor (CCKBR) are expressed within the endocrine domain of the developing pancreas (Larsson et al 1976, Suissa et al 2013. In post-natal life, pancreatic gastrin and CCKBR expression declines along with b-cell neogenesis (Rooman et al 2001, Suissa et al 2013. Ectopic expression of gastrin and transforming growth factor alpha in the pancreas or administration of gastrin in combination with epidermal growth factor or glucagon-like peptide 1 analogues has been shown to increase the b-cell mass and/or to improve glucose tolerance (Wang et al 1993, Rooman et al 2002, Suarez-Pinzon et al 2005, 2008a, supporting a potential role of gastrin in the treatment of diabetes.…”
mentioning
confidence: 99%
“…Gastrin initiates beta cell neogenesis and activation of GLP-1 signalling enhances its effect Gastrin is known to be expressed in the developing pancreas whereas it is not expressed in adult pancreas [27,28], suggesting its possible role in pancreatic endocrine development. To investigate whether or not gastrin can induce beta cell neogenesis in the adult pancreas, exo-lacZ and exo-Glp1r mice were treated with gastrin and exendin-4 using the same protocol as above (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Gastrin is expressed in the developing pancreas, particularly in endocrine populations [27,28]. Although several reports have shown that combination therapy with gastrin and growth factors, such as EGF and TGF-α, increased beta cell mass [41][42][43][44][45], there was no evidence that gastrin could induce beta cell neogenesis as distinguished from beta cell replication.…”
Section: Discussionmentioning
confidence: 99%